16 Ideal-physio: a new tool guiding innovation and evaluation of complex interventions and enacting the EBM-manifesto in physiotherapy. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Paez, Arsenio; McColluch, Peter; Hirst, Allison; Beard, David
Abstract : Objectives: IDEAL-Physio, developed from the IDEAL framework, is a new tool fulfilling key aspects of the EBM manifesto in complex interventions such as physiotherapy. Research in physiotherapy has flourished, with 24 236 clinical trials and systematic reviews added to the Physiotherapy Evidence Database between 2004−2016, but study quality, reproducibility, and relevance to patients and end-users varies widely and clinical practices with poor or no evidence continue to proliferate. The IDEAL-Physio framework seeks to improve this, proposing that innovation and evaluation in clinical practice should evolve together in an ordered manner, from conception to validation by appropriate clinical trials. This sequential, practicable framework supports an innovation pathway that is transparent, fosters quality improvement, and expands the role of patients and practicing clinicians in healthcare research. IDEAL-Physio helps bridge the gap between clinical practice and academic research, facilitating clinician participation in evidence-gathering and development, and encouraging the next generation of leaders in evidence-based healthcare. Method: The Ideal-Physio framework has five stages; Idea (1), Development (2a), Exploration (2b), Assessment (3), and Long-term study (4). Each stage has stage-specific methodological recommendations and research reporting guidelines. Research items fit within this ordered structure, helping to provide an evidence-based introduction of innovation and a transparent method of evaluating existing treatments in the context of patient-centred, evidence-based care. IDEAL-Physio advocates careful monitoring, documentation, and incorporation of patient and clinician experiences and responses to the intervention, facilitating the development of clinical practices of greater relevance to patients and end-users. Determination of whether interventions are safe, efficacious, and worthy of further use (or study) in the early IDEAL-Physio stages improves the quality of patient care and reduces research waste. Ideal-Physio encourages early, structured and systematic data collection using appropriate outcome measures. It also facilitates documentation of all modifications made in the development and implementation of the intervention, facilitating transparency and research reproducibility. Results: The IDEAL framework is successfully embedded in the surgical sciences and the medical devices field. It's latest adaptation, IDEAL-Physio, was developed to reflect the multifaceted nature of physiotherapy as a similar, practitioner-based complex intervention. The IDEAL-Physio framework was recently published in the February 2018 issue of 'Physical Therapy, ' the Journal of the American Physical Therapy Association. Clinical trials of innovative physiotherapy practices, guided by the framework, are currently underway in the United States. It is also being used as a framework for introducing concepts in evidence-based health care and the development of clinical trials by students in a doctoral program in physiotherapy for practicing clinicians at Northeastern University in Boston, Massachusetts. IDEAL-Physio is making important contribitions to patient safety and ethical practice by helping to address the current lack of rigorous evaluation and data for many clinical practices that risks patient safety and ultimately reduces patients' autonomy and informed decision-making. Conclusions: An ageing population, growing numbers with chronic diseases, and increasing emphasis on physical activity are increasing the demand for physiotherapy and other complex interventions. The need for new and existing practices that are evidence-based and patient-centred is pressing. Practicable, specific recommendations to guide rigorous evaluation of clinical practices and empower clinicians to become active participants in improving the body of evidence and quality of patient care are greatly needed. These, and other key elements of the EBM-Manifesto can be promoted in physiotherapy by IDEAL-Physio, which can also serve as a model for evidenced innovation in practice in other complex interventions.